2014
DOI: 10.1260/1369-4332.17.6.881
|View full text |Cite
|
Sign up to set email alerts
|

Settlement Monitoring of a Supertall Building Using the Kalman Filtering Technique and Forward Construction Stage Analysis

Abstract: Excessive and unexpected settlement of supertall buildings during the construction stage may affect structural safety. Floor settlement monitoring is imperative during the structural construction. The current practice is to measure floor settlement within a specific time frame and then compensate for the elevation error in the next construction stage. This posterior manner is inaccurate because it does not take account of measurement error and the real settlement in the next construction stage. This paper pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…Su et al 134 proposed an integrated construction settlement monitoring method combining the Kalman filtering approach and the FE forward construction stage analysis (Figure 8). This method was applied to the 632‐m‐tall Shanghai Tower.…”
Section: In‐construction Monitoringmentioning
confidence: 99%
See 1 more Smart Citation
“…Su et al 134 proposed an integrated construction settlement monitoring method combining the Kalman filtering approach and the FE forward construction stage analysis (Figure 8). This method was applied to the 632‐m‐tall Shanghai Tower.…”
Section: In‐construction Monitoringmentioning
confidence: 99%
“…Settlement monitoring results of Shanghai tower at different construction stages 134 . (a) Elevation of the eighth floor core‐wall.…”
Section: In‐construction Monitoringmentioning
confidence: 99%
“…Xiong et al proposed that a novel subregional least squares method should be used to calculate the horizontal displacement of frame-core-tube structures with strengthened stories [12]. Furthermore, Su et al reported a settlement monitoring approach based on the Kalman filter, which has been demonstrated to improve the accuracy of the predetermined elevation of supertall buildings through construction settlement monitoring of the 632-meter-tall Shanghai Tower [13].…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, as the building technology develops, super-tall structures have been constructed all over the world which relieves the pressure caused by the shortage of land resources. A complete SHM system has been applied on the 600-m tall Canton tower (Su et al, 2014; Xia et al, 2014). Data were collected to analyze and evaluate the structural safety condition.…”
Section: Introductionmentioning
confidence: 99%